Assessment of genetic diversity and phenotypic trait profiles among sweetpotato using singlenucleotide polymorphism (SNP) markers and agronomic variables - Abed, J.N.; Ibitoye, D.O.; Afuape, S.O.; Olasanmi, B.; Mushoriwa, H.; Agre, A.P. (2025)
Sweetpotato is an important global crop of food and nutritional significance and rural income generation, especially in Africa. Although, the crop is well adapted to diverse agroecological conditions, its genetic and phenotypic diversity is yet to be well explored. In this study, the diversity of 72 sweetpotato genotypes were assessed using phenotypic traits and single nucleotide polymorphism (SNP) markers. Genotypes differed significantly for phenotypic traits (P ≤ 0.001) such as number of leaf lobes and vine internode length. Storage root weight had strong positive correlation to commercial root yield (r > 0.80). Principal component analysis showed that the first seven components with eigenvalues > 1 explained 75.68% of the total variation among the sweetpotato genotypes. Cluster analysis grouped the genotypes into four major clusters with cluster I exhibiting the highest genetic diversity. Fifteen genotypes were identified as top-ranking using the Multi Trait Genotype Ideotype Distance Index (MGIDI). Analysis of SNP markers revealed observed heterozygosity to be between 0.00 and 0.85 and expected heterozygosity between 0.09 and 0.50. The Bayesian Information Criterion (BIC) identified four genetic clusters with cluster 1 having the largest number of genotypes. Results from both phenotypic and genotypic evaluations were complementary and facilitated the identification of superior sweetpotato genotypes with potential for breeding improvement.